Riwayat hidup dan perjuangan 20 ulama besar Sumatera Barat (Penerbitan (Islamic Centre Sumatera Barat), 1981)
Biographies of 20 well-known Muslim ulamas in West Sumatra and their contributions towards the founding of Islamic religious schools in the area.